Characterization and Detection of Endolysin Gene from Three Acinetobacter baumannii Bacteriophages Isolated from Sewage Water - Kitti, Thawatchai (Springer India, 2014)
Acinetobacter baumannii is an opportunistic pathogen that exists in hospital environments. The emergence of multidrug resistant A. baumannii (MDRAB) has been reported worldwide. It is necessary to find a novel and effective treatment for MDRAB infection. In this study, three bacteriophages, designated as ØABP-01, ØABP-02 and ØABP-04 were selected for analysis. Transmission electron microscopy showed that bacteriophage ØABP-01 belonged to the Podoviridae family and bacteriophage ØABP-02 and ØABP-04 are classified into the family Myoviridae. ØABP-01 had the widest host range. ØABP-01, ØABP-02 and ØABP-04 exhibited a latent period of 15, 20 and 20 min. The burst sizes of the three bacteriophages were 110, 120 and 150 PFU/cell. DNA restriction analysis using EcoRI, HindIII, PstI, SphI, BamHI and SmaI showed different DNA fragment patterns between the three bacteriophages. ØABP-01 and ØABP-04 was positive for the endolysin gene as determined by PCR. In conclusion, bacteriophage ØABP-01 showed broad host-specificity, good lytic activity and a short latency period, making it an appropriate candidate for studying the control and diagnosis associated with MDRAB infections.